Efforts to Increase the Number of Murabahah Financing Customers Through Marketing Strategies at Bank Muamalat Bacan Branch, South Halmahera District - Jamil, Jumrah; Hanafi, Tarisa Daeng; Bambang, Intan; Supriyanto, Putri Haliza; Syuhada, Sitti Minarsi (International Journal of Managemen Analytics (IJMA), 2023)
This research aims to determine the marketing strategy carried out by Bank Muamalat, Bacan Branch, and South Halmahera Regency to increase the number of murabahah financing customers. The type of research that the author conducted was descriptive qualitative, namely descriptive qualitative field research. Based on the results of research conducted by the author at Bank Muamalat, Bacan Branch, South Halmahera Regency, efforts to increase the number of murabahah financing customers through marketing strategies are through products, which is done by offering the advantages of murabahah financing products to the public to attract public interest in carrying out murabahah financing. at Bank Muamalat Bacan Branch, South Halmahera Regency. As for the marketing strategy through price, even though prices are considered less competitive than other financial institutions, Bank Muamalat, Bacan Branch, and South Halmahera Regency offer customers a fast process and easy terms. The results of this research show that Bank Muamalat, Bacan Branch, South Halmahera Regency has implemented an effective marketing strategy, this is proven by the increase in the number of customers again in 2023. The obstacles faced by Bank Muamalat, Bacan Branch, and South Halmahera Regency in marketing murabahah financing include transportation costs.